Unprecedented conformational flexibility revealed in the ligand‐binding domains of the Bovicola ovis ecdysone receptor (EcR) and ultraspiracle (USP) subunits. (1st July 2014) - Ren, Bin; Peat, Thomas S.; Streltsov, Victor A.; Pollard, Matthew; Fernley, Ross; Grusovin, Julian; Seabrook, Shane; Pilling, Pat; Phan, Tram; Lu, Louis; Lovrecz, George O.; Graham, Lloyd D.; et al.
<x xml:space="preserve">Abstract</x> The heterodimeric ligand‐binding region of the Bovicola ovis ecdysone receptor has been crystallized either in the presence of an ecdysteroid or a synthetic methylene lactam insecticide. Two X‐ray crystallographic structures, determined at 2.7 Å resolution, show that the ligand‐binding domains of both subunits of this receptor, like those of other nuclear receptors, can display significant conformational flexibility. Thermal melt experiments show that while ponasterone A stabilizes the higher order structure of the heterodimer in solution, the methylene lactam destabilizes it. The conformations of the EcR and USP subunits observed in the structure crystallized in the presence of the methylene lactam have not been seen previously in any ecdysone receptor structure and represent a new level of conformational flexibility for these important receptors. Interestingly, the new USP conformation presents an open, unoccupied ligand‐binding pocket.